The effect of balanced versus unbalanced football small-sided games on decision-making in youth football players - Ihle, Andreas (2021)
Decision-making (DM) is an important ability targeted in the formation of young football players that can improve by using small-sided games (SSGs). The main purpose of this study was to assess players’ DM in different balanced and unbalanced SSG formats keeping the play area constant. The sample was composed of 10 field players plus 2 goalkeepers (13.55±0.51 years). This study consisted of 3 sessions, one day for each session, with an interval of 48 hours apart between sessions. Three different SSG formats (4vs.4; 4vs.5; 4vs.6), in a play area of 40x30 meters, were selected. The outcome was the decision-making index (DMI), assessed with the Game Performance Assessment Instrument (GPAI). Results showed that on two of the three days, there were statistical differences in DMI across the three different SSG formats. In the 4vs.6 format a higher median score than in the 4vs.4 format was recorded on day 2 (U=13.0, z=-2.34, p=.025, r=.57) and day 3 (U=5.50, z=-2.98, p=.003, r=.72). In conclusion, the use of unbalanced SSG formats in the training may benefit DM development, and therefore may constitute an important factor to be considered in the formation of young football players.